Reflections on the group dynamic in a group cognitive behavioral therapy intervention for young adult women with moderate to severe dysmenorrhea: a qualitative analysis - Laura C. Seidman; Ariel B. Handy; Catherine R. Temme; Shelly F. Greenfield; Laura A. Payne (Taylor & Francis Group, 2023)
A recent group cognitive behavioral therapy (gCBT) intervention for dysmenorrhea conducted by our team demonstrated feasibility, acceptability, and preliminary efficacy at reducing menstrual pain. This study aimed to use qualitative analyses to explore participants' reflections about the intervention's group dynamic. Participants included 20 young women ages 18-24 years with average menstrual pain of 8.0 (SD = 1.1) on a 0-10 (0 = none, 10 = worst pain possible) numeric rating scale. Semi-structured individual and group interviews were conducted after the intervention. Researchers then conducted deductive, iterative thematic analysis using a template analysis approach. Two themes were generated: benefit and logistics. The benefit theme included two sub-themes: (1) camaraderie (an emotional, psychological, or social connection between participants); and (2) sharing (information, advice, or experiences). The logistics theme highlighted how the structure of the group influenced the dynamic and was divided into two sub-themes according to the time frame being described: (1) reactions (participants' experiences with how the group dynamic was facilitated); and (2) future (how the group structure could be improved). Results of this study contribute to the growing body of literature related to gCBT for pain conditions. Future research is needed to optimize the group dynamic and evaluate its specific therapeutic role in the treatment.